Glyphosate-Resistant Sourgrass Management Programs Associating Mowing and Herbicides - RAIMONDI,R.T. (2020)
ABSTRACT: Currently, sourgrass is one of the most important weeds in grain production areas in Brazil. The objective of this work was to evaluate the efficiency of associated systems composed by mowing and chemical control against clumped sourgrass. In the first experiment, different mowing heights (0, 5, 10, 15 and 20 cm), coupled with complementary applications of glyphosate + clethodim, were evaluated on sourgrass control. The second experiment was composed by programs starting with fallow mowing at different times, 50 (early), 35 (intermediate) and 20 (late) days before soybean sowing. After mowing, treatments were followed by herbicide applications according to the need until soybean harvest. The shorter the mowing height associated with herbicide application, the better the control of sourgrass. The weed management programs (anticipated, intermediate and late) were efficient on sourgrass control during fallow and along soybean cycle. Weed management programs starting with mowing provided better or similar control compared to systems that employed chemical control only, indicating that mowing can replace one of the herbicide applications.